Similar Representations of Sequence Knowledge in Young and Older Adults: A Study of Effector Independent Transfer - Barnhoorn, Jonathan S.; Döhring, Falko R.; Van Asseldonk, Edwin H. F.; Verwey, Willem B. (Frontiers in Psychology, 2016)
Older adults show reduced motor performance and changes in motor skill development. To better understand these changes, we studied differences in sequence knowledge representations between young and older adults using a transfer task. Transfer, or the ability to apply motor skills flexibly, is highly relevant in day-to-day motor activity and facilitates generalization of learning to new contexts. By using movement types that are completely unrelated in terms of muscle activation and response location, we focused on transfer facilitated by the early, visuospatial system. We tested 32 right-handed older adults (65 – 74) and 32 young adults (18 – 30). During practice of a discrete sequence production task, participants learned two 6-element sequences using either unimanual key-presses (KPs) or by moving a lever with lower arm flexion-extension (FE) movements. Each sequence was performed 144 times. They then performed a test phase consisting of familiar and random sequences performed with the type of movements not used during practice. Both age groups displayed transfer from FE to KP movements as indicated by faster performance on the familiar sequences in the test phase. Only young adults transferred their sequence knowledge from KP to FE movements. In both directions, the young showed higher transfer than older adults. These results suggest that the older participants, like the young, represented their sequences in an abstract visuospatial manner. Transfer was asymmetric in both age groups: there was more transfer from FE to KP movements than vice versa. This similar asymmetry is a further indication that the types of representations that older adults develop are comparable to those that young adults develop. We furthermore found that older adults improved less during FE practice, gained less explicit knowledge, displayed a smaller visuospatial working memory capacity and had lower processing speed than young adults. Despite the many differences between young and older adults, the ability to apply sequence knowledge in a flexible way appears to be partly preserved in older adults.